A mesh-free Monte-Carlo method for simulation of three-dimensional transient heat conduction in a composite layered material with temperature dependent thermal properties. (April 2018) - Bahadori, Reza; Gutierrez, Hector; Manikonda, Shashikant; Meinke, Rainer
Highlights: A mesh free Monte‐Carlo nonlinear transient conduction for composite media is derived. Thermal diffusivity of the particle path from source to sink is taken into account. Small numbers of emitted particles yields accurate result with less than 1% error. Simulation results are verified against FEM and experimental measurements. Abstract: A new solution for the three-dimensional transient heat conduction from a homogeneous medium to a non-homogeneous multi-layered composite material with temperature dependent thermal properties using a mesh-free Monte-Carlo method is proposed. The novel contributions include a new algorithm to account for the impact of thermal diffusivities from source to sink in the calculation of the particles' step length (particles are represented as bundles of energy emitted from each source), and a derivation of the three-dimensional peripheral integration to account for the influence of material properties around the sink on its temperature. Simulations developed using the proposed method are compared against both experimental measurements and results from a finite element simulation.